Comparison of Preparedness Levels of High School Students in Facing Disasters in West Java Province - Marlyono, Setio Galih; Triyanto, Samuel Agus (Universitas Pendidikan Indonesia, 2023)
The logical consequence of the natural state of West Java province, prone to disasters, requires humans there to be ready to deal with it. This includes senior high school students who get the material on disaster mitigation in schools and must be prepared to deal with disasters in their respective regions. The critical level of preparedness will minimize the possibility of losing a life. The research objective is to analyze the level of readiness of high school students in West Java province in the face of the three disasters that often occur in each region. The approach in this study uses quantitative descriptive with a survey method. The results showed that the level of preparedness of students in Garut for landslides has a score of 19.00, categorized Ready; the students in Tasikmalaya for earthquake disaster had the smallest value, namely, 18.88, categorized Ready, and the students in Pangandaran district for tsunami had the highest score is 22.32 and categorized Ready. In conclusion, there are significant differences in the preparedness of students in Garut, Tasikmalaya, and Pangandaran District.